Genome-Wide Identification and Expression Analysis of the Class III Peroxidase Gene Family in Potato (Solanum tuberosum L.) - Yang, Xuanshong; Yuan, Jiazheng; Luo, Wenbin; Qin, Mingyue; Yang, Jiahan; Wu, Weiren; Xie, Xiaofang (Frontiers in Genetics, 2020)
Class III peroxidases (PRXs) are plant-specific enzymes and play important roles in plant growth, development and stress response. In this study, a total of 102 nonredundant PRX gene members (StPRXs) were identified in potato (Solanum tuberosum L.). They were divided into 9 subfamilies based on phylogenetic analysis. The members of each subfamily were found to contain similar organizations of the exon/intron structures and protein motifs. The StPRX genes were not equally distributed among chromosomes. There were 57 gene pairs of segmental duplication and 26 gene pairs of tandem duplication. Expression pattern analysis based on the RNA-seq data of potato from public databases indicated that StPRX genes were expressed differently in various tissues and responded specifically to heat, salt and drought stresses. Most of the StPRX genes were expressed at significantly higher levels in root than in other tissues. In addition, real-time quantitative PCR (qRT-PCR) analysis for 7 selected StPRX genes indicated that these genes displayed various expression levels under abiotic stresses. Our results provide valuable information for better understanding the evolution of StPRX gene family in potato and lay the vital foundation for further exploration of PRX gene function in plants.